Improvement in the quality of life and pain intensity among workers with shoulder impingement syndrome after application of the Isostretching method - Barbosa, Érica Carvalho; Peres, Claudia Maria; Lucca, Sérgio Roberto de; Oliveira, José Inácio de (Acta Fisiátrica, 2012)
Among Work-Related Musculoskeletal Disorders, the Shoulder Impingement Syndrome (SIS) is the leading cause of work disability. Aside being off work, many cases often require physiotherapy. The Isostretching method can be an alternative and can contribute to improving the quality of life of workers with SIS. Objective: To verify the effects of a treatment protocol based on the Isostretching method in individuals with SIS, in improving the quality of life and decreasing pain intensity. Method: By analyzing patient records in treatment at the occupational health clinic and other Unicamp clinics, 30 volunteers were selected and submitted to 12 physiotherapy sessions with the Isostretching method for 6 weeks. The volunteers were evaluated before and after the proposed protocol using the SF-36 quality of life questionnaire and a visual numeric pain scale. Data was analyzed using (ANOVA) variance analysis, which was performed using software R, version 2.12.0. Results: The results of the SF-36 quality of life questionnaire showed statistically significant differences (p < 0.05) in most areas. In the visual numeric scale from zero to ten, the average value was 6.63 points pre-treatment and 3.23 post-treatment, which was significant (p < 0.05). Conclusion: The proposed protocol was effective in improving the quality of life and in reducing pain in the group of volunteers studied.